Inflammation and olfactory loss are associated with at least 139 medical conditions - Leon, Michael; Troscianko, Emily T.; Woo, Cynthia C. (Frontiers in Molecular Neuroscience, 2024)
Olfactory loss accompanies at least 139 neurological, somatic, and congenital/hereditary conditions. This observation leads to the question of whether these associations are correlations or whether they are ever causal. Temporal precedence and prospective predictive power suggest that olfactory loss is causally implicated in many medical conditions. The causal relationship between olfaction with memory dysfunction deserves particular attention because this sensory system has the only direct projection to memory centers. Mechanisms that may underlie the connections between medical conditions and olfactory loss include inflammation as well as neuroanatomical and environmental factors, and all 139 of the medical conditions listed here are also associated with inflammation. Olfactory enrichment shows efficacy for both prevention and treatment, potentially mediated by decreasing inflammation.